A Reply to Wielenberg on a Timeless First Cause - Craig, William L. (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2021)
Erik Wielenberg seeks to advance his critique of the kalām cosmological argument by putting forward three further criticisms of the view that God is temporal since the moment of creation. It is seen that these criticisms are misconceived and do not take cognizance of what I have written elsewhere.